False sugar sequence phenomenon and structural analysis of a-hederin and hederacoside C through electrospray ionization and multi-stage tandem mass spectrometry (2011)
ABSTRACT: Saponins are glycosides regularly found in plants, and they are frequently analyzed by means of electrospray ion sources and tandem mass spectrometry (ESI/MSn), not only to obtain an overall molecular weight through the high sensitivity of mass spectrometry, but also to obtain their structural information. The use of modern analytic techniques (such as ESI/MSn) aids the discovery and quality control assessment of new molecules found in botanicals; however, some rearrangements have been described for oligosaccharides that produce an incorrect elucidation of the molecules. For the first time, evidence for an internal sugar loss on the protonated fragmentation of a-hederin has been reported. This phenomenon can be avoided by using alkali metal ion adducts, such as lithium and sodium cations, to confirm the real sugar sequence when a structural identification is performed. In this study, the structural characterization of a-hederin and hederacoside C is conducted by comparing positive and negative modes. Different fragmentation patterns occur, and such patterns are useful in the structural analysis of saponins when they are present on different matrixes.